Spain: From massive immigration to vast emigration? - Mario Izquierdo; Juan F. Jimeno; Aitor Lacuesta (IZA Journal of Migration, 2016)
Large immigration flows during the 1995-2007 period increased the weight of foreigners living in Spain to 12 % of the total population. The rapid increase in unemployment associated with the Great Recession and the subsequent European debt crisis, substantially changed migration flows, so that, from the beginning of the 2010s, Spain experienced positive net outflows. In this paper, we take on three tasks. First, we show that sensitivity of migration flows to unemployment is similar between Spaniards born in Spain and foreigners that entered in Spain during the last 20 years. Second, we estimate the importance of past network effects of foreigners and the recent network effects of Spaniards in shaping these migration flows. Finally, we will use these estimations to conjecture that the rapid creation of networks of Spaniards abroad might keep their emigration rates growing, thus counterbalancing the effects of outflows due to the recent fall in the unemployment rate.
Keywords: F22; J64; J61; 330; Migration inflows and outflows; Unemployment; Networks